MODEL PEMBELAJARAN AL-QUR’AN HADITS DALAM MEMBENTUK KECERDASAN SPIRITUAL SISWA DI SMP WAHID HASYIM MALANG - Kintan Berliana Chaniago; Muhammad Hanif; Dian Mohammad Hakim (VICRATINA, 2022)
Learning Al-Qur'an Hadith is one of the support materials in the formation of spiritual intelligence because it emphasizes the behavior of the student. One of the problems that arises among high school students, including SMP Wahid Hasyim Malang, is the lack of training of the spiritual intelligence of the students. Based on these issues, the researchers are interested in further investigating on the following objectives: Describe and analyze (1) Al-Qur'an Hadith's learning design to shape the spiritual intelligence of students in Wahid Hasyim Junior High School Malang (2) Al- Qur'an Hadith learning process in training students' spiritual intelligence in Wahid Hasyim Malang High School (3) Al-Qur'an Hadith learning model in training of spiritual intelligence of students at Wahid Hasyim Malang High School In this study, the researchers used a descriptive qualitative approach and the type of research used The research used is a case study with the aim of presenting a complete picture of the relationship among the phenomena tested. The results show that the learning design has variations in the implementation design, the learning process of Al-Qur'an Hadith that can form spiritual intelligence in religious activities programs, it is recognized that the learning process is more effective and the Al-Qur'an Hadith learning The Wahid Hasyim High School model uses the Cooperative Contextual Model (CTL). And the TGT learning model that can shape students' emotional intelligence in various aspects at Wahid Hasyim Junior High School Malang.